Exploring the Potential of CLIL in Kazakhstan: A Qualitative Study - Huertas-Abril, Cristina A.; Shashken, Aigerim (Revista Complutense de Educación, 2021)
In the process of implementing multilingual policies, especially the so-called “Trinity of Languages Program”, the Republic of Kazakhstan is making efforts to use multilingual education as a key tool for achieving linguistic proficiency in three languages: Kazakh, Russian, and English. Being a transitional situation, where hot debates are taking place, the use of Content and Language Integrated Learning (CLIL) can be an interesting approach due to its dynamism, flexibility, and adoptability to the Kazakh context. The introduction of CLIL in the Kazakh educational system, however, has not been studied sufficiently, and it is seen as a new approach in the country. After presenting the state of the art in this Central Asia country, this qualitative research examines the perceptions, concerns and uncertainties of Kazakh teachers regarding the potential implementation of the CLIL approach in Kazakhstan. In order to analyse the data collected, we followed the grounded-theory scheme to establish the different categories and topics, we applied content analysis, and finally we create a manual SWOT analysis. Despite the challenges that teachers face regarding CLIL (mainly related to low language proficiency and lack of materials), the respondents point out that CLIL increases interest among students, students understand better the language component of the lessons, and CLIL meets the current system of modern requirements of educational standards of Kazakhstan.